Standardization of Amarantha hair oil with special reference to identification of β-sitosterol as major component having 5α-reductase inhibitory activity/hair growth promoting activity - Keshwar, Unmesh S.; Nipanikar, Sanjay U.; Kasabe, Ankita R.; Patil, Priyanka B. (International Journal of Research in Dermatology, 2021)
Background: Androgenetic alopecia is a common form of hair loss in both men and women. Synthetic drugs like minoxidil and finastride are available treatment for androgenetic alopecia, however, use of these drugs on long term basis may cause many side effects. Hence there was a need to have an effective and safe alternative option. Ari Healthcare Pvt. Ltd. has developed Amarantha hair oil (herbal hair oil) to be used for dandruff, hair fall and premature greying of hair. The aim was to standardize Amarantha hair oil with special reference to identification of β-sitosterol as major component having 5α-reductase inhibitory activity/hair growth promoting activity. Methods: Amarantha hair oil was prepared by using various herbal ingredients which contains β-sitosterol as active marker compound. Amarantha hair oil was evaluated for appearance, weight per ml, refractive index, acid value, saponification value, peroxide value, TLC Identification of β-sitosterol, assay of β-sitosterol content using high performance thin layer chromatography (HPTLC) and microbiological tests. Also accelerated stability study was performed. Results: All the parameters tested were within normal limits. Amarantha hair oil was stable in accelerated stability study. We found that almost all the ingredients of formulation contain β-sitosterol when analysed using HPTLC. Amarantha hair oil contains 0.52% of β-sitosterol. Conclusions: All the ingredients and Amarantha hair oil contain β-sitosterol that helps in promotion of hair growth.